I Gelati, i Gessi e Edgar Allan Poe - Gardi, Andrea (Venezia Arti, 2020)
The article tries to exemplify the possible work of research and contextualization one can make on an isolated and not immediately understandable source: in this specific case, an encrypted ownership mark put on a sixteenth-century printed book. Starting with mark deciphering, the work reconstructs the writers’ biographic deeds, their social position and the cultural milieu in which they acted, trying to look both at the little-known mentality of a family from little Bolognese nobility between sixteenth and seventeenth century, and at the possible social spread (in a period thought to be characterised by conformism and mind control) of cultural elements bound to hermeticism, neoplatonism, qabalah, alchemy, magic, heterodoxy; a spread which was promoted by some academies and religious orders.